Community Knowledge and Attitudes about the Transmission of Dengue Haemorrhagic Fever and Its Relationship to Prevention Behaviour in Palembang, South Sumatra, Indonesia - Minarti, Minarti; Anwar, Chairil; Irfannuddin, Irfannuddin; Irsan, Chandra (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: PSN 3 M Plus is a long-running program in Indonesia for the prevention and control of dengue hemorrhagic fever (DHF). AIM: This study aimed to determine the knowledge, behavior, attitudes, and beliefs of the community toward PSN 3 M Plus in preventing and controlling the spread of DHF. METHODS: A cluster random sampling method was used to recruit 200 respondents in endemic areas and 100 respondents in sporadic locations of Indonesia from August 2020 to February 2021. The respondents were interviewed directly by interviewers and the relationships between demographics and characteristics with the practice of PSN 3M Plus prevention behavior on the incidence of DHF were analyzed. RESULTS: Most respondents had good knowledge regarding the cause of DHF. Although respondents recognized and understood the dangers of and how to control DHF, most did not follow PSN 3 M Plus and believed that fogging was the most effective control measure. There was a significant relationship between the characteristics of the respondents in terms of education, occupation, and attitude on vector control practice. CONCLUSION: Although community environmental modifications can be a cost-effective approach to reduce the incidence of DHF, there is a need to raise public awareness regarding preventive vector control measures as good knowledge does not guarantee good compliance with PSN 3M Plus recommendations.